DIFFERENCES IN INTERLEUKIN 18 LEVELS IN DIABETIC NEPHROPATHY AND NON-DIABETIC NEPHROPATHY PATIENTS - Rizka Sari Anggawaty Hrp, Alwi Thamrin Nst & Ratna Akbari Ganie (International Journal of Research Science and Management, 2020)
Background: Diabetic nephropathy is a common complication in diabetics. In this disease damage to the kidney filter or known as glomerulus. Therefore causing glomerular damage, the amount of blood protein is excreted into the urine abnormally. IL-18 is a proinflammatory cytokine produced from activated macrophages, serum IL-18 levels are produced to increase in patients with diabetic nephropathy. IL-18 which affects the production of other proinflammatory cytokines, endothelial apoptosis, ICAM-1 certification enhancement. Thus, IL-18 may be an important factor not only in the process of atherosclerosis but also in the development of diabetic nephropathy. Aim: Knowing the IL-18 levels in diabetic nephropathy and non-diabetic nephropathy patients. Methods: The study was conducted using the Cross Section method. This study took blood samples from 60 diabetic patients, of which 30 patients with nephropathy and 30 patients with type 2 diabetes. Then took 5 ml of blood from a vein and assessed serum IL-18 levels in all patients. Results: The study was conducted for 3 months, 41 men (68.3%) 19 women (37.1%). Serum IL-18 levels were significantly increased in patients with diabetic nephropathy compared with patients with type 2 diabetes (362.7 vs 55.7 pg / ml, p <0.001) Conclusions: Increased IL-18 levels in diabetic nephropathy patients can be used as prognostic events for diabetic nephropathy